The print media and crime: values and issues (2007)
That the press sensationalizes crime stories, over reports violent crime stories like homicide, assault etc in comparison to non-violent stories and that violent stories are usually reported disproportionately compared to their incidence in official crime statistics or victim surveys, and that sensational reporting of crime contribute to concern over crime among the public is point of concern. This stimulates fear of crime which is now being recognized as a distinct social problem and issue for public debate. This paper examines the print media and the creation of fear of crime, amount and sources of crime in the print media and patterns of crime reporting bringing out some core values. The paper acknowledges reporting of crime as epidemic and examines some vital suggestions towards uplifting the values of the press in crime reporting. The paper concludes that print media play vital roles in shaping public perception of risk factors in criminality, crimes, stimulate public awareness and impact on the criminal Justice system, Therefore, concern for such issues and values of the media in crime reporting could also help in preventions and control of criminalities.